POLA PERMUKIMAN NELAYAN TRADISIONAL BERBASIS MATA PENCAHARIAN DI CEMPAE KOTA PAREPARE - Ni’mah Natsir (Nusantara Hasana Journal, 2025)
The settlements in Cempae are shaped by the daily activities of the community, particularly in relation to fishing. The settlement patterns are directly connected to water bodies and village roads, with the sea serving as the central orientation. The location and form of traditional fishing settlements in Cempae are influenced by the inhabitants' occupations. A prevalent issue today is the development of new settlements located far from workplaces, with designs that do not reflect the residents' professions. This often leads to rejection and abandonment of these new settlements. Therefore, research is needed to explain the influence of livelihoods on fishing settlement patterns. This study aims to analyze the patterns of traditional fishing settlements in Cempae that align with fishing livelihoods. The research employs a descriptive qualitative method with direct surveys to the settlement locations, providing detailed descriptions of the existing conditions. The results show that livelihoods influence the patterns of traditional fishing settlements in Cempae, as seen in the orientation of buildings facing the source of livelihood, namely the sea.